A MOMENT METHOD FORMULATION FOR THE ANALYSIS OF WIRE ANTENNAS ATTACHED TO ARBITRARY CONDUCTING BODIES DEFINED BY PARAMETRlC SURFACE - Rivas, F. (Applied Computational Electromagnetics Society Journal (ACES), 2022)
A Moment Method (MM) technique for the analysis of wire antennas on board resonant-sized bodies modelled with parametric surfaces is presented. The approach may have useful applications for the study of the behaviour of wire antennas on board complex conducting structures like aircrafts. The current is represented by curved rooftop functions on the body, piecewise linear functions on the wires and a new junction function in the attachment region between the body and the antenna. The bodies are precisely defined by means of a small number of NURBS surfaces (Non Uniform Rational B-Splines) and Bezier patches (BP). In addition the new junction function that can be defined over any BP allows the antenna to be attached to any part of the body. Radiation patterns and input impedance calculations for several geometries are presented to show the accuracy of the method. The results are successfully validated when comparisons with measurements or results from other methods are carried out. [Vol. 11, No. 2 (1996), pp 32-39